Core effect of local atomic configuration and design principles in AlxCoCrFeNi high-entropy alloys. (15th March 2020) - Yang, Yu-Chia; Liu, Cuixia; Lin, Chun-Yu; Xia, Zhenhai
Abstract: High-entropy alloys (HEAs) are known to have four core effects leading to superior properties over traditional alloys. In this paper, we investigate an additional core effect, local atomic configuration, due to inherent variations of local chemical composition at the nanoscale. The stacking fault and twin formation energies of Alx CoCrFeNi HEAs, calculated with density functional theory methods, show large variations and even negative energies due ro the local atomic configurations. A design principle is proposed to predict the mechanical properties of the HEAs. The effect of temperature on stacking fault energy is also determined, which is consistent with experimental results. Graphical abstract: Image, graphical abstract